The Cambridge guide to English literature - Stapleton, Michael (Cambridge University Press, 1983)
The purpose of this book is to provide a guide to the literature of the English-speaking world in a single volume. It covers more than a thousand years and includes the literature of Great Britain, the United States, Australia, Canada and New Zealand; the English writing from Ireland and South Africa, and the new and exciting contributions from the West Indies and Nigeria since the Second World War. This book offers the reader more than facts. However, facts are essential: the entries begin with these and all-important dates will also be found. The lives of many writers are intrinsically interesting as well as significant to their work, and in cases where the details are known they are given at some length. Major works of poetry, fiction, drama, satire, history, philosophy and religion are described; so are the outstanding characters created by our major writers. A host of subjects and terms merit entries of their own - metrical romances, metaphysical poetry, the Marprelate controversy, the closure of the playhouses: picaresque, latitudinarianism and transcendentalism are some of them. Two major ones, The English Language and The Bible in English, were specially commissioned. Encompasses more than three thousand entries representing writers, their works, and memorable characters.